Formative assessment lessons for concept development and problem solving - Swan, Malcolm; Foster, Colin (2018)
Formative assessment is the process by which teachers and students gather evidence of learning and then use this to adapt the way they teach and learn in the classroom. In this paper we describe a design research project in which we integrated formative assessment into mathematics classroom materials. We outline two examples of formative assessment lessons, one concept-based and the other problem-solving, highlighting the important roles within them of pre-assessment, formative feedback questions and sample work for students to critique